Long-stay in forensic-psychiatric care in the UK - Hare Duke, Laurie; Furtado, Vivek; Guo, Boliang; Völlm, Birgit Angela (Springer Verlag, 2018)
Purpose: Forensic services provide care for mentally disordered offenders. In England this is provided at three levels of security – low, medium and high. Significant number of patients within these settings remain detained for protracted periods of time. This is both very costly and restrictive for individuals. No national studies have been conducted on this subject in England. Methods: We employed a cross-sectional design using anonymised data from medical records departments in English secure forensic units. Data was collected from a large sample of medium secure patients (n=1572) as well as the total high secure patient population (n=715) resident on the census date (01.04.2013). We defined long-stay as a stay of more than 10 years in high, five years in medium or 15 years in a mix of high and medium secure settings. Long-stay status was assessed against patient demographic and admission information. Results: We identified a significant proportion of long-stayers: 23.5% in high secure and 18.1% in medium secure care. Amongst medium secure units a large variation in long-stay prevalence was observed from 0 to 50%. Results indicated that MHA section, admission source and current ward type were independent factors associated with long-stay status. Conclusion: This study identified a significant proportion of long-stayers in forensic settings in England. Sociodemographic factors identified in studies in individual settings may be less important than previously thought. The large variation in prevalence of long-stayers observed in the medium secure sample warrants further investigation.